PENTINGNYA PENDAFTARAN PANGAN INDUSTRI RUMAH TANGGA (PIRT) BAGI USAHA KECIL MENENGAH DI DESA MRAHU, KECAMATAN KARTOHARJO, MAGETAN - Anik Tri Haryani; Krista Yitawati; Sarjiyati; Yuni Purwati (JURNAL DAYA-MAS, 2023)
The purpose of this service is to provide community understanding and assistance regarding the importance of registration of home industry food (PIRT). Based on the Regulation of the Food and Drug Supervisory Agency (BPOM) Number 22 Year 2018 concerning Guidelines for the Provision of Household Industry Food Certificates, it is explained that the notion of PIRT is a Certificate of Household Industry Food Permit (PIRT) given by the Regent or Mayor through the Health Office. This certificate refers to that the food produced produced has met the specified security requirements and standards. Institutions that have the right to issue certificates or PIRT permits are regents or mayors through intermediaries from the Health Office. The certificate will be given to the Food Household Industry or SMEs that have met certain security requirements and standards, in the process of making and distributing food products to provide SPP-IRT (Household Industry Food Production Certificate).